Radio-Telemetric Assessment of Cardiac Variables and Locomotion With Experimentally Induced Hypermagnesemia in Horses Using Chronically Implanted Catheters - Schumacher, Stephen A.; Toribio, Ramiro E.; Lakritz, Jeffrey; Bertone, Alicia L. (Frontiers in Veterinary Science, 2019)
The objective of this study was to characterize the pharmacokinetics and pharmacodynamics of intravenous administration of magnesium sulfate to horses using a novel radio-telemetry system for physiologic signal capture. Five Horses were surgically implanted with a radio-telemetric carotid catheter. Implants were paired with a non-invasive telemetric unit which acquired a six lead ECG and 3-axis acceleration to assess activity acquired wirelessly in real-time for future analysis. Horses were exposed to a new stall environment before (baseline) and after 60 mg/kg (30 mL) of magnesium sulfate (MgSO4), or the same volume of 0.9% saline, administered intravenously in a blinded, random crossover design. Blood for pharmacokinetics, telemetric data, and body temperature were recorded serially for 24 h. Data were analyzed across time and between treatments. Significance was set at P < 0.05. Ionized magnesium concentration (Mg2+) increased and the Ca2+ to Mg2+ ratio decreased and persisted for 5 h after MgSO4 administration. Heart rate (HR) increased and mean arterial blood pressure (MAP) decreased for at least 6 h. Electrocardiogram (ECG) intervals (RR) decreased and (PR and QTc) increased in duration compared to controls indicating an increase in heart rate, and slower myocardial conduction in the MgSO4 group. Acceleration in all planes was less in the MgSO4 group compared to controls indicating decreased locomotion. This novel method permitted collection of physiologic signals without interference by handlers or animal restraint. An intravenous bolus of MgSO4 produced cardiac variable changes associated with the reduction of locomotion in these horses, and in a direction that may be causal. Locomotion was decreased when horses were first introduced into a new environment which reflects the calming effect desired in sport horses. Telemetric monitoring can be used as a model to elucidate the behavior and physiologic effects of other drugs. The administration of MgSO4 may be detected for regulatory purposes with the monitoring of Mg2+ and Ca2+ concentrations and their ratio.